Identification of Cayenne Pepper Plant Pest Organisms (OPT) - sembiring, Desi sri pasca sari; Amardi, Jento; Tarigan, Utomo Relmana; Tarigan, Restu Bremana; Simangunsong, Bintang Mangoloi; Sinulingga, Aldy Hernanda; Tarigan, Rivanly Kemri (Universitas Serambi Mekkah, 2025)
This study aims to identify organisms that interfere with cayenne pepper plants in Telagah Village, Seibingei District, Lalat Regency. The method used is a survey method with a data collection approach in the form of direct observation of the expanse of chili plants. Based on the results of the research that has been carried out, the results of the identification of Plant Pest Organisms in chili plants in Telagah Village are yellow virus, anthracnose fruit rot, fruit and leaf rot, whitefly, weeds (puzzle grass, and grass weeds). Based on the results of the research, the conclusion obtained was that plant pest organisms were found in the form of whitefly aphids, fruit flies, walang sangit/leafhoppers, harleyquin ladybugs and aphids, there were also 5 types of diseases found in cayenne pepper plants, namely fruit rot, stem rot, bule disease/yellow virus, curly virus and leaf spot.